Deskripsi Pengetahuan, Sikap, dan Praktik Perawat tentang Manajemen Nyeri Prosedur Invasif pada Pasien Anak - Ferika Indarwati; Kinanti Kinanti; Dewi Caesaria Fitriani; Rahmah Rahmah (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Knowledge, attitudes, and practices of nurses on pediatric pain management of invasive procedures are important aspects of nursing competencies. Children are usually unable to express pain accurately, hence these competencies are vital to ensure pain in pediatric patients is addressed appropriately.  However, there is still limited research on this topic. The aim of this study was to understand the knowledge, attitudes and practices of nurses about the pain management of invasive procedures in pediatric patients. This study employed a cross-sectional approach and conducted in two hospitals in Yogyakarta with a total sample of 63 pediatric nurses. Valid questionnaire with 12 demographic data questions, 12 nurse knowledge questionnaire questions, 13 nurse attitude questionnaire questions, and 10 nurse practice questions was used. Nurses' knowledge scores on pain management of invasive procedures in pediatric patients was relatively high with an average score of 10.11 (84%), the attitude score about the management of pain of invasive procedures in children was in the relatively in good category with an average score of 48.52 or (68.31%) and the nurse's practice on pain management of invasive procedures in children was still suboptimal with an average score of 38.87 or (72%). Nurses have relatively good knowledge in handling the pain of invasive procedures in pediatric patients, while the nurse’ attitudes and practices are still not optimal. Therefore, nurse’ competencies in this aspect should be imroved to ensure high quality of nursing care in pediatric pateints.